Indigenous Food and Nutrition Knowledge and Practice among Ethnocultural Groups in Nepal: A Narrative Review - Upreti, Yadu Ram; Sharma, Tribhuwon; Sharma, Prakash (Mangal Research Journal, 2025)
Indigenous food and nutrition knowledge and practice (IFNKP) represent intergenerational learning, environmental stewardship, and cultural uniqueness. In Nepal, diverse ethnic groups such as the Tharu, Danuwar, Darai, Majhi, Rai, Limbu, Magar, Gurung, Chepang, Tamang, Newar, Sherpa, Thakali, and Loba possess distinct IFNKP linked to their local ecology. This narrative review aimed to explore indigenous foods as sources of nutritional requirements, traditional food and nutrition knowledge among ethnic groups, and indigenous food practices within these communities. Literature published between 2020 and 2025 was reviewed through Google Scholar, Scopus, and Web of Science, yielding 28 peer-reviewed studies that met the inclusion criteria. The information was analyzed under three themes, and the major finding shows that indigenous foods such as Dhido, Gundruk, Kinema, and Bhakka provide significant dietary fiber, protein, and antioxidant benefits while remaining culturally acceptable. Traditional technologies such as fermentation, sun-drying, and steaming help sustain food value and reduce foodwaste. However, these practices are gradually diminishing due to dietary shifts, urbanization, and insufficient policy recognition. The review highlights that IFNKP is not an antiquated tradition but a living practice that shapes dietary behavior and nutritional status among Nepali tribal groups. Integrating IFNKP into Nepal’s nutrition and education policies, supporting local farming, promoting knowledge transfer, and addressing climate change can help preserve indigenous food culture and improve community health and food security.